Changes in Lower Limb Muscle Activation and Degree of Weight Support according to Types of Cane-Supported Gait in Hemiparetic Stroke Patients. (23rd September 2020) - Choi, Eun Pyeong; Yang, Seong Ju; Jung, A. Hyun; Na, Hye Su; Kim, Yeong Ok; Cho, Ki Hun
Abstract : This study was aimed at investigating the changes in the degree of weight support loaded on the cane and paretic-side lower limb muscle activation according to the types of cane and cane-supported gait using a weight-support feedback cane (WSFC). Eleven hemiparetic stroke patients were recruited from a local rehabilitation hospital. WSFC can measure the degree of weight support loaded on the cane during cane-supported walking in units of kg, through a force sensor installed inside the handle. This study measured the degree of weight support loaded on the cane and lower limb muscle activation under four conditions: two-point and three-point gait with mono and quadripod canes. In the two-point gait with mono and quadripod canes, subjects were asked to move the WSFC and paretic-side foot forward at the same time and then move the nonparetic-side foot. In the three-point gait with mono and quadripod canes, subjects were asked to first move the WSFC forward, then the paretic-side foot, and finally the nonparetic-side foot. The degree of weight support loaded on the cane was significantly higher in the three-point gait with WSFC than in the two-point gait with WSFC for both mono (P = .047 ) and quadripod canes (P = .002 ). Additionally, the paretic-side lower limb muscle activation during the stance phase was significantly higher in the two-point gait with WSFC than in the three-point gait with WSFC for both mono (P = .008 ~ .044 ) and quadripod canes (P = .008 ~ .026 ). Our results suggest that applying the three-point gait with high cane dependence in the early stages of training for stability and subsequently applying the two-point gait for the enhancement of lower limb muscle activation and training of normal gait pattern could be effective.